Taking command of continuity-An interview study with agency nurses - Ingrid Djukanovic; Cecilia Fagerström; Kristina Schildmeijer; Hanna Tuvesson (Wiley, 2023)
Abstract Aim The aim of the study was to describe continuity from the perspective of working as an agency nurse (AN). Design Qualitative design was applied using individual semi‐structured interviews. Method Individual interviews with fifteen registered nurses working at agency companies were conducted in 2020. The interviews were analyzed with thematic analysis. The study followed the guidelines addressed in the COREQ (Consolidated Criteria for Reporting Qualitative Research) framework. Results Thematic analysis yielded one theme ‐ standing strong and taking command ‐ and four categories: being competent and experienced, being prepared and at ease, ensuring an unbroken chain of care, and belonging on my own terms. The categories illustrated the engagement, professionalism, and natural leadership showed by the ANs to uphold quality and continuity.